2015
DOI: 10.1101/cshperspect.a023051
|View full text |Cite
|
Sign up to set email alerts
|

The Perinatal Microbiome and Pregnancy: Moving Beyond the Vaginal Microbiome

Abstract: The human microbiome, the collective genome of the microbial community that is on and within us, has recently been mapped. The initial characterization of healthy subjects has provided investigators with a reference population for interrogating the microbiome in metabolic, intestinal, and reproductive health and disease states. Although it is known that bacteria can colonize the vagina, recent metagenomic studies have shown that the vaginal microbiome varies among reproductive age women. Similarly, the richnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
89
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 171 publications
(238 reference statements)
2
89
1
7
Order By: Relevance
“…15,16 Another mechanism could be the microbiome, where intestinal flora develop differently according to delivery mode (as the baby born by caesarean section does not pass through the bacterial milieu of the vaginal canal or is exposed to antibiotics routinely given at caesarean section), resulting in different postnatal development of the immune system. 17 Given the uncertainty and opposing nature of the hypothesised mechanisms, we held no a priori hypothesis about the direction of the effect of caesarean on schooling. Although we did not hypothesise a specific pathway towards schooling, this study excludes a large impact of delivery on child development.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Another mechanism could be the microbiome, where intestinal flora develop differently according to delivery mode (as the baby born by caesarean section does not pass through the bacterial milieu of the vaginal canal or is exposed to antibiotics routinely given at caesarean section), resulting in different postnatal development of the immune system. 17 Given the uncertainty and opposing nature of the hypothesised mechanisms, we held no a priori hypothesis about the direction of the effect of caesarean on schooling. Although we did not hypothesise a specific pathway towards schooling, this study excludes a large impact of delivery on child development.…”
Section: Discussionmentioning
confidence: 99%
“…The vaginal mucosa is a barrier that provides protection against pathogenic infections through the interaction between its epithelial cells, the immune system, and colonizing microorganisms (Figure ) . The composition of the female genital tract microbiota is influenced by many factors including age, vaginal pH, hormonal secretions, the menstrual cycle, contraceptives, antibiotic use, and sexual activity . The microbial composition of a woman′s genital tract varies over time, according to her estrogen production .…”
Section: Introductionmentioning
confidence: 99%
“…The early life environment is thought to influence the development of obesity, with recent attention focusing on the microbiome. Inoculation of the newborn gut by vaginal and gastrointestinal microorganisms occurs during vaginal but not cesarean births, offering a potential mechanism linking cesareans with obesity . A recent systematic review suggested that cesarean was associated with 0.44 higher BMI (95% CI 0.17, 0.72) but was unadjusted for confounding .…”
mentioning
confidence: 99%